Death on the argyle - Canadeo, Anne, 1955- (Canadeo, Anne, 1955- Black sheep knitting mystery., 2022)
As one of the Black Sheep Knitters prepares to become a mother, a new member becomes a suspected killer... Spring has reached Plum Harbor, Massachusetts, and the weather isn't the only thing that's changing. Eight months pregnant, Lucy prepares to enter an exciting phase in life while weaving together loose threads from her past. It feels like fate when she reconnects with college friend Rebecca Hurley, whose eclectic Happy Hands Cafe is the perfect locale for Black Sheep gatherings. But just as charming Rebecca joins their closely knit circle, she's suspected of murder. It appears to be an accident when Rebecca's writer husband, Colin, is crushed by a fallen bookcase at the cafe. But his death is quickly determined to be murder. Adding to the horror, police believe Rebecca committed a heinous act of revenge against Colin for planning to end their marriage--a move that would cut off Rebecca's contact with the stepdaughter she adores. Despite the incriminating evidence growing faster than her belly, Lucy is convinced that she must prove her old friend's innocence. As her due date approaches and a dangerous mystery unravels, Lucy and the Black Sheep shift from knitting baby booties to chasing down the cunning culprit who's always a few steps ahead.